Patient perspectives of the impact of psoriatic disease on quality-of-life in India: Sub-analysis from the global psoriasis and beyond survey - B S Chandrashekar; Chitra S Nayak; Bikash R Kar; Vineeth Salloju (Indian Dermatology Online Journal, 2024)
Background: Psoriatic disease (PsD), including plaque psoriasis (PsO) and psoriatic arthritis (PsA), comprises a wide spectrum of manifestations and significantly impacts quality-of-life (QoL). Here, we assessed patients' understanding of PsO and PsA as a systemic disease, its impact on their physical and emotional well-being, and patients' experiences with healthcare professionals for shared treatment decision-making. Materials and Methods: The Global Psoriatic Disease and Beyond Survey was a cross-sectional, qualitative, online survey conducted on patients with moderate-to-severe PsO with/without concomitant PsA. This analysis reports findings from Indian patients. Results: Of the 261 surveyed patients, 27% with PsO reported concomitant PsA, of whom 89% reported PsA severity as moderately or highly active. Overall, 92% had heard the term “PsD,” and 90% knew their condition was a systemic disease. Few were aware of PsD manifestations (palmoplantar psoriasis, 49%; nail psoriasis, 43%; axial symptoms, 40%; PsA, 34%) and comorbidities (cardiovascular disease, 33%; obesity, 30%; diabetes, 28%). Eighty-nine percent of patients indicated their skin problems had a “very-large” to “extreme-large” impact on QoL. Ninety-seven percent of patients experienced discrimination and stigmatization from others. Eighty-one percent of patients were not involved in deciding treatment goals. Few (PsO, 6%; PsA, 9%) patients were dissatisfied with current treatment; ≥50% patients reported incomplete relief of skin symptoms (PsO) and joint symptoms (PsA) as the reason for dissatisfaction. Conclusion: Lack of awareness of the manifestations and comorbidities associated with PsD and poor QoL highlights the need for patient education, shared treatment decision-making, and a multidimensional approach to PsD management in India.